Comparison of 18F-AlF-NOTA-FAPI and 18F-FDG Imaging in a Patient With Gastric Signet-Ring Cell Carcinoma. (November 2021) - Guo, Yue-Hong; Yang, Min-Fu
Abstract : Abstract: Several case reports have shown fibroblast activation protein inhibitor (FAPI) imaging to be superior to 18 F-FDG imaging in the delineation of primary gastric signet-ring cell carcinoma lesions. In this case, 18 F-AlF-NOTA-FAPI PET/CT showed more metastatic lesions that had more increased activity than 18 F-FDG PET/CT. However, neither 18 F-AlF-NOTA-FAPI nor 18 F-FDG imaging revealed any abnormal uptake in the primary gastric lesion, which was subsequently demonstrated to be the primary lesion by pathology.